A Level Playing Field – An Optimal Weighting Scheme of Dismissal Protection Characteristics - Michael Kind (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
In the case of collective redundancies, employers are forced to regard certain characteristics when deciding who is going to be dismissed. This paper develops a procedure to derive an empirical based weighting scheme between the characteristics relevant for this selection (age, disability, dependencies and tenure). First, panel data from the German Socio-Economic Panel (SOEP) for the years 1991-2010 is used to estimate, conditional on the existence of dismissal protection, the relationships of the four characteristics with respect to reemployment probabilities and the quality of the new job (measured in terms of wage). Second, the individual valuation of the two outcomes is compared applying a life satisfaction analysis. Finally, based on the empirical results a weighting scheme for the characteristics is proposed, which serves as an evidence based guideline for employers, employees and unions in the process of collective redundancies. – – Wenn Arbeitgeber betriebsbedingte Kündigungen durchführen, müssen sie die zu kündigenden Arbeitnehmer nach festgelegten Kriterien auswählen. Diese Studie entwickelt ein Verfahren, um ein empirisch basiertes objektives Gewichtungsschema zwischen den Selektionskriterien (Lebensalter, Schwerbehinderung, Unterhaltspflicht und Betriebszugehörigkeit) herzuleiten. Zunächst wird mit Hilfe von Daten des Sozio-ökonomischen Panels für die Jahre 1991-2010, konditioniert auf die Existenz von Kündigungsschutzregeln, der Zusammenhang zwischen den vier Charakteristika und der Wiederbeschäftigungswahrscheinlichkeit bzw. der Qualität des neuen Jobs (gemessen durch den Lohn) geschätzt. Dann wird die individuelle Gewichtung der beiden Variablen im Rahmen einer Analyse der Lebenszufriedenheit verglichen. Basierend auf den daraus gewonnenen Erkenntnissen wird ein Gewichtungsschema der vier Kriterien vorgeschlagen, welches in zukünftigen Kündigungsentscheidungen für Arbeitgeber, -nehmer und Gewerkschaften als Grundlage dienen kann.
Keywords: J63; J64; 330; dismissal protection; reemployment probability; wage hit